Research on the oxygen and humidity related-electrical behavior of monolayer MoS2 under vacuum to normal pressures. (23rd July 2021) - Li, Meng; Shi, Huiyao; Jin, Xiaoshi; Wang, Lu; Liu, Xi; Wu, Meile
Abstract: Molybdenum disulfide (MoS2 ) has recently gained tremendous research interest due to its distinctive properties. A comprehensive understanding of the performance of MoS2 across a complete range of pressures is significant from the perspective of practical application. While extensive research has been conducted to explore the potential of MoS2 under extremely high pressures, there is still a lack of deep insights into how it performs under vacuum to normal pressures. In this experimental study, we examine the electrical behavior of MoS2 as the pressure varies from vacuum pressure to standard atmospheric pressure in N2 and O2, respectively. The I – V measurements show that higher pressures induce faster oxygen adsorption of MoS2 . In addition, the investigation into the effect of humidity reveals that humidity has a greater influence on the electrical behavior of MoS2 than oxygen.